The social construction of adolescence in contemporaneity - Isidório, Marcelo S. (Sociological studies of children and youth, 2023)
Multifactorial perspectives, whether sociological, cultural, anthropological, historical, biological or psychological, serve as the basis for a considerable amount of research, including how youth and adolescents are influenced by the sociocultural aspects that guide the way they are seen and see the society around them. For researchers and scholars who focus on this subject, it is worth asking: what characterizes adolescence as a social construction in different regions of the planet? The Social Construction of Adolescence in Contemporaneity considers the social field of adolescence in different societies. Recognizing external cultural or societal factors that can influence individual development, contributors discuss a variety of regional traits that can characterize this group, reflecting on the concept of adolescence as a phenomenon of its own in the field of sociology. Expanding this area of youth studies across specific contexts, The Social Construction of Adolescence in Contemporaneity offers new interpretive possibilities to deepen the understanding of issues that concern young people.